2012
DOI: 10.1159/000343730
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-5 Inhibitors Could Be Efficacious in the Treatment of Erectile Dysfunction after Radiotherapy for Prostate Cancer: A Systematic Review and Meta-Analysis

Abstract: Objective: This systematic review was performed to evaluate the efficacy and safety of phosphodiesterase-5 inhibitors (PDE5i) in the treatment of erectile dysfunction (ED) after radiotherapy for prostate cancer (PCa). Methods: A systematic search of PubMed, Embase and the Cochrane Library was performed to identify all randomized controlled trials (RCTs). All relevant studies on the outcomes and complications of PDE5i in the treatment of ED after radiotherapy for PCa were assessed. The outcomes and complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Furthermore, several studies evaluated the sexual function of diabetic patients, generally using the international index of erectile function (31). However, also in this area, no agreement exists on the questionnaire to use, as other studies report the sexual encounter profile (32) or the structured interview of erectile dysfunction (SIEDY) (33).…”
Section: Data Collection Process and Qualitymentioning
confidence: 99%
“…Furthermore, several studies evaluated the sexual function of diabetic patients, generally using the international index of erectile function (31). However, also in this area, no agreement exists on the questionnaire to use, as other studies report the sexual encounter profile (32) or the structured interview of erectile dysfunction (SIEDY) (33).…”
Section: Data Collection Process and Qualitymentioning
confidence: 99%
“…As a result, with a corresponding increase in cavernosal tumescence and rigidity, smooth muscle relaxation is enhanced and blood inflow into the corpora cavernosa. 6,15 As the first oral selective phosphodieterase type5 (PDE5) inhibitor, the introduction of sildenafil in 1998 is an important advance in the treatment of ED. 16 Two other PDE5 inhibitors, vardenafil and tadalafil, were also developed in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Study outcomes vary considerably among patients on ADT, making recommendations for this group problematic. There have been mixed findings of sildenafil usage in this group [45] although a 2013 article concluded that PDE5 inhibitors were safe and efficacious [46]. Low libido and motivation may limit recruitment into these trials compared with postradical prostatectomy studies [47].…”
Section: Adt Patientsmentioning
confidence: 99%